Genotipic coefficient of determination for characters of nine rubber tree clones - Ribeiro, Sydney Itauran; Ventorim, Nelson; Pereira, Péricles; Bueno, Luis C. de S. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to determinate the genotipic determination coefficient, in a wide sense, for nine quantitative characters, in the fix set of nine rubber tree clones. The clones were obtained from crosses and primary selection of Hevea spp. The experimental design was in randomized complete blocks with nine treatments and three replications. The following characters were studied: dry rubber production by early Hamaker Morris-Mann (HMM) test, total plant height, stem circunference at 1.30 m and 0.50 m from the point of insertion of the graft, back thicknees, total number of latex vessels rings, diameter of latex vessels, density of latex vessels per 5 mm rings and average distance between consecutive vessels rings. Genotipic determination coefficient estimates based upon plot means, in a wide sense, were high for all characters, except for diameter of latex vessels. This indicate that both traits are quite important in rubber trees improvement programs.